[PP.20.03] LINKING ENDOTHELIAL DYSFUNCTION TO THE BIOLOGICAL PROFILE OF INFLAMMATION AND COAGULATION AT HYPERTENSIVE PATIENTS WITH OR WITHOUT DIABETES MELLITUS. (September 2017) - Gavrila, A.; Florea, M.; Ciobanu, M.; Pritulescu, C.; Persu, R.; Sosea, I.; Rosu, A.
Abstract : Objective: The objective of the study was to estimate how the pro-inflammatory and pro-thrombotic imbalances correlate with endothelial dysfunction at hypertensive patients (pts) with or without diabetes mellitus (DM). Design and method: 40 hypertensive pts (mean age 58.4 ± 7.3 years, 52.5% males) group 1 and 40 hypertensive pts with DM, matched for age and sex (mean age 56.5 ± 7.6 years, 55% males) group 2.Endothelial function was evaluated using ultrasound assessment of flow mediated vasodilatation of the brachial artery (FMD). FMD smaller than 10% was considered abnormal. Inflammation profile was estimated by serum measurement of C reactive protein (CRP) and fibrinogen (F). Pro-thrombotic profile was determinated by serum measurement of von Willebrand factor (vWf), antithrombin III (AT III), plasminogen activator inhibitor (PAI 1) and homocysteine (H). Results: In group 1, 13 pts (32.5%) had reduced FMD (%): 7.3 ± 1.6. In group 2, 16 pts (40%) had reduced FMD (%): 6.8 ± 1.9. The difference is not significantly statistic between the two groups (p = 0.44). In group 1, reduced FMD was significantly associated with higher level of CRP (2.65 ± 1.17 mg/l vs 7.84 ± 1.68 mg/l, p = 0.02). In group 2, low FMD was found in a significantly higher proportion at pts with higher level of CRP (2.87 ± 1.33 mg/l vs 9.25 ± 2.03 mg/l, p = 0.008) and also with greater proportion of vWf (87.21 ± 31.73% vs 148.15 ± 42.33%, p = 0.001). In the same group, reduced FMD was significantly associated with higher level of PAI 1 (0.42 ± 0.24 u/ml vs 0.92 ± 0.35 u/ml, p = 0.03) and higher proportion of H (4.2 ± 1.3 μm/l vs 17.4 ± 1.2 μm/l, p = 0.02). Conclusions: Hypertensive pts with DM have endothelial dysfunction in a greater but not significant proportion than hypertensive pts without DM. Endothelial dysfunction at hypertensive pts seems to reflect a pro-inflammatory status. Moreover, endothelial dysfunction at hypertensive pts with DM appears to express both pro-inflammatory status and pro-thrombotic imbalance.